Terapi Aktivitas Kelompok (TAK) Tebak Gambar pada Lansia dengan Demensia di Panti Sosial Tresna Werdha Budi Mulia 2 - Elisha Aprilia; Annisa Rohmatun; Divani Widya; Dwi Riyaningsih; Fatmawati; Firyal Izzati Arifah; Alfika Safitri (Jurnal Pustaka Keperawatan (Pusat Akses kajian Keperawatan), 2026)
Dementia is a cognitive disorder that commonly occurs in older adults and may affect memory, concentration, thinking ability, communication, and daily activities. One non-pharmacological intervention that can be implemented to help maintain cognitive function in older adults is Group Activity Therapy (GAT). This study aims to describe the implementation of a picture-guessing therapy in improving the cognitive function of older adults. The method used was Group Activity Therapy with a picture-guessing game approach, conducted among older adults at PSTW Budi Mulia 2. The results showed that the participants were able to follow the activity well, appeared more active and focused, and demonstrated improvements in memory and concentration. In addition, this therapy had a positive impact on the participants’ mood and social interaction. Therefore, picture-guessing Group Activity Therapy can be considered a simple, safe, and applicable non-pharmacological nursing intervention to help maintain cognitive function and improve the psychosocial well-being of older adults.